Analysis of the Influence of Organizational Culture and Transformational Leadership on Employee Performance with Job Satisfaction as an Intervening Variable in PT Hutama Karya Infrastruktur Seksi Padang Sicincin - Defi Adrian; M. Isa Indrawan; Mesra B. (Yayasan Multidimensi Kreatif, 2023)
This research aims to determine the Influence of Organizational Culture and Transformational Leadership on Employee Performance with Job Satisfaction as an Intervening Variable at PT Hutama Karya Infrastruktur Padang Sicincin. The research approach used in this study is quantitative. The population in this study is all employees of PT HKI Padang Siring Section which amounts to 54 people. This study conducted a sampling technique by Non Probability Sampling, namely by using census sampling or saturated sampling because the entire population is as many as 54 employees / respondents. The data collection used is to use personal questionnaires. The data analysis technique used in this study is a path analysis technique using smart PLS software. The results showed that Perception Organizational Culture had a positive and significant effect on Employee Performance at PT HKI Padang Sicincin. Transformational Leadership has a positive and significant effect on Employee Performance at PT HKI Padang Sicincin Section. Perception Organizational Culture has a positive and significant effect on Job Satisfaction at PT HKI Padang Sicincin Section. Transformational Leadership has a positive and significant effect on Job Satisfaction at PT HKI Padang Sicincin. Job Satisfaction has a positive and significant effect on Employee Performance at PT HKI Padang Sicincin. Perception Organizational Culture has a positive and significant effect on Employee Performance through Job Satisfaction at PT HKI Padang Sicincin. Transformational Leadership has a positive and significant effect on Employee Performance through Job Satisfaction at PT HKI Padang Sicincin.